POLA BIMBINGAN DAN PENYULUHAN ISLAM BAGI MAHASISWA PADA PROGRAM PASIH STAIN PAREPARE - Ramli, Ramli; Marhani, Marhani; Nurhikmah, Nurhikmah (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2016)
PASIH STAIN Parepare as an institution is central to the development of interests, talents and expertise to improve student competence reliable so that students are able to compete into the world . Do not only become the main duties as a supervisor in charge of the program, but all the lecturers involved in the teaching and learning on campus STAIN Parepare also be a mentor as well as extension workers Advisors are required to hold approach not only through instructional approaches, but also persuasive approach in each peroses learning takes place. The constraints faced by the program PASIH STAIN Parepare include Infrastructure issues are available not maximized, Lack of student interest and time-sharing issues, guiding the implementation of the program implemented Pasih STAIN Parepare.